Polyether type high-flame-retardant halogen-free TPU material and preparation method thereof
By using boron-containing polyethylene glycol and phosphorus-containing isocyanate in polyether type TPU materials, and adding carboxylated silica and amino-graphene, the problems of insufficient tensile strength and poor heat resistance are solved, and the problem of insufficient material is achieved. High flame retardant performance and thermal stability are improved.
Patent Information
- Application Number
- CN202411793710.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The tensile strength of polyether TPU materials is insufficient, the heat resistance is poor, and the oxygen index is low during combustion, which affects its further application.
Boron-containing polyethylene glycol and phosphorus-containing isocyanate are used as raw materials, and carboxylated silica and amino-based graphene are introduced. Through the synergistic action of each component, the tensile strength and heat resistance of the material are improved, while achieving multi-element synergy Flame retardant.
The tensile strength and heat resistance of polyether TPU materials are significantly improved, and good flame retardant performance is obtained through the synergistic action of boron, phosphorus, silicon and nitrogen elements, with a 10% increase in thermal decomposition temperature and an oxygen index increase.
Smart Images

Figure SMS_4 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a polyether type highly flame-retardant halogen-free TPU material and a preparation method thereof. Background Art
[0002] Thermoplastic polyurethane (TPU) elastomer is a linear polymer formed by the interblock copolymerization of hard segments and soft segments. The carbamates in the hard segments can form intermolecular hydrogen bonds, so that the hard segments aggregate to form physical crosslinking points, providing TPU with physical properties such as tensile resistance, wear resistance and heat resistance; its soft segments are composed of polyether, polyester or their mixtures, which provide TPU with elasticity similar to rubber. When synthesizing polyether polyurethane elastomer, polyether polyurethane elastomer is synthesized by reacting polyisocyanate and polyether polyol, so that the synthesized polyurethane elastomer has a large number of ether bonds. Thanks to the excellent product performance, the application fields of TPU are constantly expanding, including daily consumer goods, construction, medical, military, automobile, agriculture and many other fields.
[0003] A Chinese patent (publication number CN118956148A) discloses a highly flame-retardant polyether TPU material and its preparation method, which can make the amino nano-silicon dioxide evenly dispersed in the TPU matrix to form physical cross-linking points by adding amino nano-silicon dioxide in the preparation of modified polyether TPU, thereby enhancing the modulus and wear resistance of TPU, and the addition of amino nano-silicon dioxide can improve the resilience, tear resistance and fatigue resistance of TPU. However, the patent does not solve the problems of insufficient tensile strength, poor heat resistance and low oxygen index during combustion of polyether TPU materials in the prior art, thus affecting the further application of TPU materials.
[0004] Therefore, how to optimize the raw materials of polyether TPU materials and introduce different modified components to effectively improve the tensile strength of the materials while giving the TPU materials good heat resistance and flame retardant properties has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a polyether-type highly flame-retardant halogen-free TPU material and a preparation method thereof, aiming to solve the problems of insufficient tensile strength, poor heat resistance and low oxygen index during combustion of polyether-type TPU materials in the prior art.
[0006] The present invention selects boron-containing polyethylene glycol and phosphorus-containing isocyanate as the synthetic raw materials of the polyether TPU material, and simultaneously introduces carboxylated silica and amino graphene. The components act synergistically to effectively improve the tensile strength of the polyether TPU material, while giving it good heat resistance and flame retardant properties.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows: The first aspect of the present invention provides a method for preparing a polyether-type highly flame-retardant halogen-free TPU material, comprising the following steps: Step S1: by weight, 50-60 parts of boron-containing polyethylene glycol are subjected to vacuum dehydration treatment, and then mixed evenly with 150-160 parts of isocyanate, and kept warm at 80-85° C. for 1-2 hours to obtain an intermediate; Step S2: adding 0.2-0.5 parts of silicon dioxide and 0.1-0.3 parts of graphene to 25-30 parts of 1,4-butanediol by weight, and uniformly dispersing by ultrasonication to obtain a mixed solution; Step S3: In parts by weight, 200-220 parts of the intermediate are heated to 95-100° C., and then 25-30 parts of the mixed solution are added and stirred for 15-20 minutes. After stirring, the mixture is poured into a mold and placed in an oven at 110-120° C. for aging for 8-10 hours to obtain a polyether-type highly flame-retardant halogen-free TPU material; The vacuum dehydration treatment conditions include: temperature of 115-118°C, vacuum degree of 120-130Pa, and time of 1-3h; The preparation method of the boron-containing polyethylene glycol comprises: In parts by weight, 30-35 parts of polyethylene glycol and 3-5 parts of boric acid are mixed, stirred at 120-130° C. for 40-60 minutes, then 5-10 parts of benzene are added, volatiles are removed by condensation and reflux, and the product is dried to obtain boron-containing polyethylene glycol; The isocyanate is a phosphorus-containing isocyanate; The phosphorus-containing isocyanate is selected from any one or a combination of at least two of phosphorus-containing isocyanate I, phosphorus-containing isocyanate II and phosphorus-containing isocyanate III; Wherein, the structural formula of the phosphorus-containing isocyanate I is: ; Wherein, the structural formula of the phosphorus-containing isocyanate II is: ; Wherein, the structural formula of the phosphorus-containing isocyanate III is: ; The silicon dioxide is carboxylated silicon dioxide; The preparation method of the carboxylated silicon dioxide comprises: In parts by weight, 1-2 parts of silane coupling agent KH550 and 1-2 parts of succinic anhydride are uniformly dispersed in 500-600 parts of N,N-dimethylformamide, and after stirring for 3-4 hours, 5-8 parts of silicon dioxide are added thereto, and 100-150 parts of deionized water are added thereto, and stirring is continued for 5-6 hours; after the stirring is completed, the mixture is washed with deionized water, and dried at 60-70° C. for 10-12 hours to obtain carboxylated silicon dioxide; The graphene is amino graphene; The preparation method of the amino graphene comprises: In parts by weight, 2 to 6 parts of graphene oxide are added to 500 to 600 parts of deionized water, and ultrasonic dispersion is performed to obtain a graphene oxide dispersion; 1 to 3 parts of polyethyleneimine are added to 100 to 150 parts of deionized water, and ultrasonic dispersion is performed to obtain a polyethyleneimine solution; 500 to 600 parts of the graphene oxide dispersion and 100 to 150 parts of the polyethyleneimine solution are uniformly mixed, and the mixture is stirred for reaction for 20 to 24 hours. After the reaction is completed, the mixture is centrifuged, washed with water, and dried to obtain amino graphene.
[0008] The boron element in boron-containing polyethylene glycol can form a stable protective layer during the combustion process, inhibit the spread of flames, and reduce heat release, thereby effectively improving the flame retardant properties of the material.
[0009] It should be noted that the source of the phosphorus-containing isocyanate is not particularly limited in the present invention, and the phosphorus-containing isocyanate can be purchased from the market or prepared by itself. The preparation method of the phosphorus-containing isocyanate is not particularly limited in the present invention, and can be prepared by referring to the method described in "Holtschmidt H, Oertel G. Isocyanates of Esters of Some Acids of Phosphorus and Silicion [J]. Angewandte Chemie International Edition, 2010, 1 (12): 617-621."
[0010] During combustion, the phosphorus-based groups in phosphorus-containing cyanates will produce phosphaphenanthrene groups in the gas phase, which can capture the free radicals of the gas-phase cracking gas, form a stable structure, exert the free radical quenching effect, and improve the flame retardant efficiency; at the same time, phosphorus-containing isocyanates contain benzene ring structures, with large intermolecular steric hindrance, large chemical bond energy, and good thermal stability of the material, which can effectively improve the heat resistance.
[0011] The carboxyl group of carboxylated silica can react with the active groups in polyether TPU to form chemical bonds and enhance interfacial interactions. At the same time, the carboxyl group can promote the uniform distribution of silica. Through good interfacial interactions and uniform dispersion, stress can be effectively transmitted and the tensile strength of the material can be improved.
[0012] The amino groups on the surface of amination graphene can adsorb with the polar groups in the polyether TPU material through physical effects such as hydrogen bonds, further enhancing the interfacial interaction. At the same time, graphene can also absorb and disperse impact energy, thereby significantly improving the tensile strength of the TPU material.
[0013] The second aspect of the present invention provides a polyether-type highly flame-retardant halogen-free TPU material prepared by the method described in the first aspect.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The amino groups on the surface of the aminated graphene in the present invention can be adsorbed with the polar groups in the polyether TPU material through physical effects such as hydrogen bonds, further enhancing the interfacial interaction. At the same time, the graphene can also absorb and disperse the impact energy, thereby significantly improving the mechanical properties of the material. The carboxyl groups of the carboxylated silica can react with the active groups in the polyether TPU to form chemical bonds, enhancing the interfacial interaction. At the same time, the carboxyl groups can promote the uniform distribution of silica. Through good interfacial interaction and uniform dispersion, stress can be effectively transmitted, thereby improving the tensile strength of the TPU material.
[0015] (2) The boron element in the boron-containing polyethylene glycol of the present invention can combine with the nitrogen element in the amino graphene to form a three-dimensional network structure, which can effectively dissipate heat and reduce the formation of local hot spots, thereby increasing the thermal decomposition temperature of the polyether TPU material when the thermal mass loss is 10%.
[0016] (3) The present invention can form a polyether TPU material by reacting boron-containing polyethylene glycol and phosphorus-containing isocyanate, and adds modified components such as carboxylated silica and amino graphene to achieve multi-element synergistic flame retardancy of boron, phosphorus, silicon and nitrogen in the TPU material; wherein the boron element can form a glass-like protective film or a heat-insulating coke layer at the combustion temperature, thereby isolating the air or preventing heat conduction; the phosphorus element can form a protective layer that isolates oxygen and combustibles and covers the surface of the material; the silicon element can easily migrate to the surface of the material at high temperature and form a silicate layer, preventing the escape of combustion decomposition products and inhibiting the thermal decomposition of the material; the nitrogen element can dilute the oxygen concentration in the air, thereby reducing the rate of the combustion reaction. Good flame retardancy is obtained through the joint action of multiple elements such as boron, phosphorus, silicon and nitrogen. DETAILED DESCRIPTION
[0017] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0018] The sources of some components in the embodiments and comparative examples are as follows: Polyethylene glycol, catalog number PA73288, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Isocyanate, CAS No. 75-13-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; 1,4-Butanediol, CAS No. 110-63-4, purchased from Sinopharm Chemical Reagent Co., Ltd.; Silicon dioxide, catalog number zkky7767653-0135, was purchased from Beijing Zhongke Keyou Technology Co., Ltd.; Graphene oxide, model AGO, was purchased from Guangzhou Amy Graphene Technology Co., Ltd.; Boric acid, CAS No. 11113-50-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Benzene, CAS No. 71-43-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Silane coupling agent KH550, product number RB1032, was purchased from Shanghai Huicheng Biotechnology Co., Ltd.; Succinic anhydride, CAS No. 108-30-5, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; N,N-dimethylformamide, CAS No. 68-12-2, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Polyethyleneimine, product number 9002-98-6, was purchased from Guangzhou Meigu Chemical Co., Ltd.
[0019] Preparation of boron-containing polyethylene glycol: By weight, 35 parts of polyethylene glycol and 5 parts of boric acid are mixed, stirred at 120° C. for 60 minutes, then 10 parts of benzene are added, volatiles are removed by condensation and reflux, and the product is dried to obtain boron-containing polyethylene glycol.
[0020] Preparation of carboxylated silica: 2 parts of silane coupling agent KH550 and 2 parts of succinic anhydride were weighed and uniformly dispersed in 600 parts of N,N-dimethylformamide. After stirring for 4 hours, 8 parts of silica were added thereto, and 150 parts of deionized water were added, and stirring was continued for 6 hours. After stirring, the mixture was washed with deionized water and dried at 70°C for 10 hours to obtain carboxylated silica.
[0021] Preparation of amino graphene: In parts by weight, 6 parts of graphene oxide are added to 600 parts of deionized water, and ultrasonic dispersion is performed to obtain a graphene oxide dispersion; 3 parts of polyethyleneimine are added to 150 parts of deionized water, and ultrasonic dispersion is performed to obtain a polyethyleneimine solution; 600 parts of the graphene oxide dispersion and 150 parts of the polyethyleneimine solution are mixed evenly, stirred for reaction for 24 hours, and after the reaction is completed, centrifuged, washed with water, and dried to obtain amino graphene.
[0022] Example 1 This embodiment provides a method for preparing a polyether-based highly flame-retardant halogen-free TPU material, comprising the following steps: Step S1: 60 parts by weight of boron-containing polyethylene glycol are subjected to vacuum dehydration treatment (temperature: 118° C., vacuum degree: 130 Pa, time: 1 h), and then mixed evenly with 160 parts of phosphorus-containing isocyanate I, and kept at 85° C. for 2 h to obtain an intermediate; Step S2: adding 0.5 parts of carboxylated silicon dioxide and 0.3 parts of amino graphene to 30 parts of 1,4-butanediol by weight, and uniformly dispersing by ultrasonication to obtain a mixed solution; Step S3: In parts by weight, 220 parts of the intermediate are heated to 100° C., and then 30 parts of the mixed solution are added and stirred for 20 minutes. After stirring, the mixture is poured into a mold and placed in an oven at 120° C. for aging for 8 hours to obtain a polyether-type highly flame-retardant halogen-free TPU material.
[0023] Example 2 This embodiment provides a method for preparing a polyether-based highly flame-retardant halogen-free TPU material, comprising the following steps: Step S1: 50 parts by weight of boron-containing polyethylene glycol are subjected to vacuum dehydration treatment (temperature: 115° C., vacuum degree: 120 Pa, time: 3 h), and then mixed evenly with 150 parts of phosphorus-containing isocyanate II, and kept at 80° C. for 2 h to obtain an intermediate; Step S2: adding 0.2 parts of carboxylated silicon dioxide and 0.1 parts of amino graphene to 25 parts of 1,4-butanediol by weight, and uniformly dispersing by ultrasonication to obtain a mixed solution; Step S3: In parts by weight, 200 parts of the intermediate are heated to 95° C., and then 25 parts of the mixed solution are added and stirred for 15 minutes. After stirring, the mixture is poured into a mold and placed in an oven at 110° C. for aging for 10 hours to obtain a polyether-type highly flame-retardant halogen-free TPU material.
[0024] Example 3 This embodiment provides a method for preparing a polyether-based highly flame-retardant halogen-free TPU material, comprising the following steps: Step S1: 55 parts of boron-containing polyethylene glycol were subjected to vacuum dehydration treatment (temperature: 116° C., vacuum degree: 125 Pa, time: 2 h), and then mixed evenly with 155 parts of phosphorus-containing isocyanate III, and kept at 83° C. for 2 h to obtain an intermediate; Step S2: adding 0.4 parts of carboxylated silicon dioxide and 0.2 parts of amino graphene to 28 parts of 1,4-butanediol by weight, and uniformly dispersing by ultrasonication to obtain a mixed solution; Step S3: Based on weight, 210 parts of the intermediate are heated to 98°C, and then 28 parts of the mixed solution are added and stirred for 17 minutes. After stirring, the mixture is poured into a mold and placed in an oven at 115°C for aging for 9 hours to obtain a polyether-type highly flame-retardant halogen-free TPU material.
[0025] Comparative Example 1 This comparative example provides a method for preparing a polyether TPU material, which differs from Example 1 in that commercially available polyethylene glycol is used instead of boron-containing polyethylene glycol, commercially available isocyanate is used instead of phosphorus-containing isocyanate, commercially available silica is used instead of carboxylated silica, and commercially available graphene oxide is used instead of amino graphene.
[0026] Comparative Example 2 This comparative example provides a method for preparing a polyether TPU material, which differs from comparative example 1 in that boron-containing polyethylene glycol is used instead of commercially available polyethylene glycol.
[0027] Comparative Example 3 This comparative example provides a method for preparing a polyether TPU material, which is different from comparative example 1 in that phosphorus-containing isocyanate is used instead of commercially available isocyanate.
[0028] Comparative Example 4 This comparative example provides a method for preparing a polyether TPU material, which differs from comparative example 1 in that carboxylated silica is used instead of commercially available silica.
[0029] Comparative Example 5 This comparative example provides a method for preparing a polyether TPU material, which differs from comparative example 1 in that amino graphene is used instead of commercially available graphene oxide.
[0030] Comparative Example 6 This comparative example provides a method for preparing a polyether TPU material, which differs from Example 1 in that commercially available polyethylene glycol is used instead of boron-containing polyethylene glycol.
[0031] Comparative Example 7 This comparative example provides a method for preparing a polyether TPU material, which is different from Example 1 in that commercially available isocyanate is used instead of phosphorus-containing isocyanate.
[0032] Comparative Example 8 This comparative example provides a method for preparing a polyether TPU material, which differs from Example 1 in that commercially available silica is used instead of carboxylated silica.
[0033] Comparative Example 9 This comparative example provides a method for preparing a polyether TPU material, which differs from Example 1 in that commercially available graphene oxide is used instead of amino graphene.
[0034] The TPU material properties provided in the above embodiments and comparative examples were tested, and the testing method is as follows: Tensile strength test: Test according to the requirements of GB / T 1040.1-2018 Determination of tensile properties of plastics Part 1: General.
[0035] Heat resistance test: Under nitrogen protection, the TPU material was heated from 25°C to 700°C at a rate of 10°C / min. The thermal decomposition curve was tested using a thermogravimetric analyzer (model TG209F1, NETZSCH, Germany). The thermal decomposition temperature at which the thermal mass loss in the thermal decomposition curve was 10% was used to measure the heat resistance of the material.
[0036] Flame retardant performance test: Test according to the requirements of GB / T 2406.2-2009 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test.
[0037] The above performance test data is shown in Table 1.
[0038]
[0039] From the above content, it can be seen that the present invention selects boron-containing polyethylene glycol and phosphorus-containing isocyanate as the synthetic raw materials of polyether TPU materials, and introduces carboxylated silica and amino graphene to prepare polyether high flame retardant halogen-free TPU materials (Examples 1~3). The tensile strength of the TPU material is 27.2~27.8MPa, the thermal decomposition temperature when the thermal mass loss is 10% is 312~316℃, and the oxygen index is 32.4~32.7%.
[0040] Compared with Example 1, commercially available polyethylene glycol is used to replace boron-containing polyethylene glycol, commercially available isocyanate is used to replace phosphorus-containing isocyanate, commercially available silicon dioxide is used to replace carboxylated silicon dioxide, and commercially available graphene oxide is used to replace amino graphene, then the tensile strength is reduced, the thermal decomposition temperature when the thermal mass loss is 10% is reduced, and the oxygen index is reduced (Comparative Example 1); compared with Comparative Example 1, boron-containing polyethylene glycol is used to replace commercial polyethylene glycol, and the oxygen index is increased (Comparative Example 2); compared with Comparative Example 1, phosphorus-containing isocyanate is used to replace commercially available isocyanate, and the thermal decomposition temperature when the thermal mass loss is 10% is increased (Comparative Example 3); compared with Comparative Example 1, carboxylated silicon dioxide is used to replace commercially available silicon dioxide, and the tensile strength is increased, and the thermal decomposition temperature when the thermal mass loss is 10% is increased (Comparative Example 4); compared with Comparative Example 1, amino graphene is used to replace commercially available graphene oxide. , the tensile strength increases, and the thermal decomposition temperature at a thermal mass loss of 10% increases (Comparative Example 5); compared with Example 1, commercially available polyethylene glycol is used to replace boron-containing polyethylene glycol, the tensile strength decreases, the thermal decomposition temperature at a thermal mass loss of 10% decreases, and the oxygen index decreases (Comparative Example 6); compared with Example 1, commercially available isocyanate is used to replace phosphorus-containing isocyanate, the tensile strength decreases, the thermal decomposition temperature at a thermal mass loss of 10% decreases, and the oxygen index decreases (Comparative Example 7); compared with Example 1, commercially available silica is used to replace carboxylated silica, the tensile strength decreases, the thermal decomposition temperature at a thermal mass loss of 10% decreases, and the oxygen index decreases (Comparative Example 8); compared with Example 1, commercially available graphene oxide is used to replace amino graphene, the tensile strength decreases, the thermal decomposition temperature at a thermal mass loss of 10% decreases, and the oxygen index decreases (Comparative Example 9).
[0041] In summary, the present invention selects boron-containing polyethylene glycol and phosphorus-containing isocyanate as the synthetic raw materials of polyether TPU materials, and introduces carboxylated silica and amino graphene. The components work synergistically to effectively improve the tensile strength of the polyether TPU material, while giving it good heat resistance and flame retardant properties.
[0042] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a polyether type highly flame-retardant halogen-free TPU material, characterized in that: The following steps are involved: Step S1: by weight, 50-60 parts of boron-containing polyethylene glycol are subjected to vacuum dehydration treatment, and then mixed evenly with 150-160 parts of isocyanate, and kept warm at 80-85° C. for 1-2 hours to obtain an intermediate; Step S2: adding 0.2-0.5 parts of silicon dioxide and 0.1-0.3 parts of graphene to 25-30 parts of 1,4-butanediol by weight, and uniformly dispersing by ultrasonication to obtain a mixed solution; Step S3: In parts by weight, 200-220 parts of the intermediate are heated to 95-100° C., and then 25-30 parts of the mixed solution are added and stirred for 15-20 minutes. After stirring, the mixture is poured into a mold and placed in an oven at 110-120° C. for aging for 8-10 hours to obtain a polyether-type highly flame-retardant halogen-free TPU material; The vacuum dehydration treatment conditions include: temperature of 115-118°C, vacuum degree of 120-130Pa, and time of 1-3h; The preparation method of the boron-containing polyethylene glycol comprises: In parts by weight, 30-35 parts of polyethylene glycol and 3-5 parts of boric acid are mixed, stirred at 120-130° C. for 40-60 minutes, then 5-10 parts of benzene are added, volatiles are removed by condensation and reflux, and the product is dried to obtain boron-containing polyethylene glycol; The isocyanate is a phosphorus-containing isocyanate; The phosphorus-containing isocyanate is selected from any one or a combination of at least two of phosphorus-containing isocyanate I, phosphorus-containing isocyanate II and phosphorus-containing isocyanate III; Wherein, the structural formula of the phosphorus-containing isocyanate I is: ; Wherein, the structural formula of the phosphorus-containing isocyanate II is: ; Wherein, the structural formula of the phosphorus-containing isocyanate III is: ; The silicon dioxide is carboxylated silicon dioxide; The preparation method of the carboxylated silicon dioxide comprises: In parts by weight, 1-2 parts of silane coupling agent KH550 and 1-2 parts of succinic anhydride are uniformly dispersed in 500-600 parts of N,N-dimethylformamide, and after stirring for 3-4 hours, 5-8 parts of silicon dioxide are added thereto, and 100-150 parts of deionized water are added thereto, and stirring is continued for 5-6 hours; after the stirring is completed, the mixture is washed with deionized water, and dried at 60-70° C. for 10-12 hours to obtain carboxylated silicon dioxide; The graphene is amino graphene; The preparation method of the amino graphene comprises: In parts by weight, 2 to 6 parts of graphene oxide are added to 500 to 600 parts of deionized water, and ultrasonic dispersion is performed to obtain a graphene oxide dispersion; 1 to 3 parts of polyethyleneimine are added to 100 to 150 parts of deionized water, and ultrasonic dispersion is performed to obtain a polyethyleneimine solution; 500 to 600 parts of the graphene oxide dispersion and 100 to 150 parts of the polyethyleneimine solution are uniformly mixed, and the mixture is stirred for reaction for 20 to 24 hours. After the reaction is completed, the mixture is centrifuged, washed with water, and dried to obtain amino graphene.
2. A polyether type highly flame retardant halogen-free TPU material, characterized in that: Prepared according to the method of claim 1.
Citation Information
Patent Citations
High-flame-retardant polyether type TPU (thermoplastic polyurethane) material and preparation method thereof
CN118956148A
Thermoplastic polyurethane elastomer for charging pile sheath and preparation method of thermoplastic polyurethane elastomer
CN114957967A
Polymer biological membrane filler and preparation method thereof
CN116253426A
High-wear-resistance polyurethane polished section and preparation process thereof
CN118027347A
Isocyanatoaryl esters and amides of phosphoric and thiophosphoric acids
GB891654A
Cited By
Flame-retardant nylon cable sheath material and preparation method thereof
CN119735947A